2.5x-1.9y=4.9
-0.5x+1.8y=4.7 Multiply this equation by 5 to obtain a first term of -2.5x:
-2.5x + 9y = 23.5 To this version of the 1st equation add the entire 2nd equation:
-2,5x + 9y = 23.5
2.5x -1.9y = 4.9
------------------------- Combine these two equations, which will eliminate x:
7.1y = 28.4 Now divide both sides by 7.1 to obtain a value for y:
y = 28.4 / 7.1 = 4
Now substitute 4 for y in either of the original equations:
2.5x - 1.9(4) = 4.9, or 2.5x = 12.5. Sovling for x, x = 12.5 / 2.5 = 5.
Then the solution is (4, 5).